Physiological and electroencephalographic changes in goats subjected to transportation, lairage, and slaughter - Othman, Azalea Hani; Goh, Yong Meng; Mohamed Mustapha, Noordin; Raghazli, Razlina; Kaka, Ubedullah; Imlan, Jurhamid Columbres; Abubakar, Ahmed Abubakar; Abdullah, Rasedee (John Wiley & Sons, 2021)
This preliminary trial investigated the effect of transportation and lairage periods on physiological parameters of goats subjected to slaughter. Nine male Boer cross goats aged 8–12 months were transported for 6 h and kept at lairage for 3, 6, or 16 h (n = 3). Blood samples were collected at pre- (pre-T) and post-transportation (post-T), and post-slaughter (post-S) for determination of hematological parameters, serum enzyme, protein, and cortisol concentrations. Electroencephalogram readings were taken at pre-T, post-T, pre-slaughter (pre-S), and post-S to determine the median frequency (F50) and total power (Ptot) values. At post-T, there were manifestations of stress leukogram; increase in hematocrit, total protein, and muscle enzyme concentrations; and decrease in Ptot (p < 0.05). The high pre-T cortisol concentration suggests that the goats were already under stress before transportation. Stress leukogram became less evident after lairage, indicating that the goats had recovered from the stress of transportation. Although the Ptot increased at post-S especially following 3 h of lairage, F50 values at post-S did not differ from pre-L, suggesting that the pre-slaughter stress may have affected the pain threshold. It is suggested that after 6 h of transportation, goats should ideally be placed in lairage for a minimum period of 3 h before slaughter.